Formação de professores de química: um olhar sobre o Pibid da Universidade Federal de Uberlândia - Bedin, Everton (2012)
This study aims to understand how the Programa Institucional de Bolsa de Iniciação à Docência da Universidade Federal de Uberlândia influences in formation of chemistry teachers in the subproject Pibid|Química|UFU. The methodology adopted for the development in the research - beyond the study of art about teacher training and programs that encourage this training it was performed a qualitative research, being a case study of ethnographic perspective, wherever was if made a fieldwork in the participants schools of Pibid|Química|UFU, who owned the subproject in chemistry area. We verified that the work done in subproject allowed the narrowing of the actions of UFU with the public schools, putting forth the knowledge for teacher training through negotiations performed in the participating schools, as well as the proposition of specific actions to be developed in the educational environment. The Pibid|Química|UFU, in this case, proved to be an important instrument of teaching professionalization, although the limitations and difficulties encountered during this investigation.